1989
DOI: 10.1136/bmj.298.6666.117-b
|View full text |Cite
|
Sign up to set email alerts
|

Is there a genetic factor in flecainide toxicity?

Abstract: surgeries and have reported our early findings.2 We extended our study to include animals for slaughter. As Drs McCarthy and Zumla refer to the organism being difficult to culture it is appropriate to present our methods, which by using a selective medium make the isolation and recognition of DF-2 organisms comparatively easy. Cotton wool tipped swabs of incisor teeth and gingival margins were placed in Amies charcoal based transport medium for delivery to the laboratory, where they were cultured using brainhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This situation is reminiscent of that described by Stuart et al where the cause of intoxication was traced back to the crystallisation of Fl after storage in a refrigerator (unfortunately, the composition of the suspending vehicle was not reported) [19]. In fact, the administration of an aliquot of a solution containing floaters of concentrated Fl may result in over-dosing rather than under-dosing.…”
Section: Chemical and Physical Stability Studymentioning
confidence: 80%
See 1 more Smart Citation
“…This situation is reminiscent of that described by Stuart et al where the cause of intoxication was traced back to the crystallisation of Fl after storage in a refrigerator (unfortunately, the composition of the suspending vehicle was not reported) [19]. In fact, the administration of an aliquot of a solution containing floaters of concentrated Fl may result in over-dosing rather than under-dosing.…”
Section: Chemical and Physical Stability Studymentioning
confidence: 80%
“…Although it is possible to administer the correct dose even from suspensions [17,18], it should be noted that the presence of a precipitate that has not been properly characterised could affect stability and bioavailability in unexpected ways. Indeed, the literature reports at least one case of intoxication due to the formation of Fl crystals [19].…”
Section: Introductionmentioning
confidence: 99%
“…Ventricular tachycardia occurred when milk feeds were substituted with dextrose feeds and the serum flecainide concentration increased from 0.99 to 1.824 µg/mL in 24 hours, demonstrating impaired absorption of oral flecainide secondary to milk feeds. Lastly, Stuart et al 12 reported on a neonate who developed flecainide toxicity after his liquid preparation was refrigerated, causing crystallization and inaccurate dosing.…”
Section: Discussionmentioning
confidence: 99%